Components of short-horizon individual security returns - Conrad, Jennifer; Kaul, Gautam; Nimalendran, M. (Journal of Financial Economics, 1991)
In this paper, we present a simple model which relates security returns to three components: an expected return, a bid-ask error, and white noise. The relative importance of the various components is empirically assessed, and the model's ability to explain the various time-series properties of individual security and portfolio returns is tested. Time-varying expected returns and bid-ask errors are found to explain substantial proportions (up to 24%) of the variance of security returns. We also reconcile the typically negative autocorrelation in security returns with the strong positive autocorrelation in portfolio returns.